Reviewing the Effectiveness of Public Service Policy Implementation to Enhance Citizen Satisfaction - Dakarai, Azibo; Tererau, Masimbu; Tariri, Fungae (Journal Social Civilecial, 2023)
This study examines the effectiveness of public service policy implementation in enhancing citizen satisfaction, with a focus on identifying socio-economic and cultural barriers that hinder the process. Using a qualitative approach, in-depth interviews were conducted with citizens and local government officials in marginalized and rural communities to explore their experiences with public services. The study reveals that while governments strive to improve service delivery, challenges such as financial constraints, digital divides, and cultural norms persist, limiting access to essential services. The findings demonstrate that existing policies often fail to address the nuanced needs of diverse populations, particularly in areas with limited resources and technological infrastructure. By analyzing the gaps between policy formulation and actual implementation, the research highlights the importance of community-based participatory approaches, inclusive communication strategies, and targeted interventions to improve the effectiveness of public service delivery. The study contributes to the ongoing discourse on public administration and governance by proposing strategies for policymakers to enhance service accessibility, ensure equity, and promote citizen-centric governance. Future research should focus on integrating digital platforms and innovative technologies in overcoming these barriers